Isolation and Molecular Characterization of Escherichia coli O157 from Broiler and Human Samples - Kalin, Recep; Ongor, Hasan; Cetinkaya, Burhan (Mary Ann Liebert Inc, 2012)
There is a lack of information about the role of poultry, specifically chicken, in transmission of Escherichia coli (E. coli) O157 and subsequent human illnesses. This study was therefore aimed at investigating the presence of E. coli O157 and its virulence genes in various samples collected from broiler chickens and humans in Eastern Turkey by culture, immunomagnetic separation (IMS), and polymerase chain reaction (PCR). The genetic relationship between broiler and human isolates was also examined by pulsed-field gel electrophoresis (PFGE). In the PCR analysis of sorbitol-negative isolates, E. coli O157 was identified in 0.1% (1/1000) and 0.4% (4/1000) of the liver and cecum samples of broiler chickens, respectively. On the other hand, none of the carcass samples were determined to be positive for E. coli O157. Overall, the results indicated that 12% (3/25) of the flocks were positive for E. coli O157. The differences between the flocks in terms of the positivity were determined to be statistically significant (p < 0.001). Ten (2.7%) of 367 human stool samples were also positive for E. coli O157 in the PCR examination. None of the broiler and human E. coli O157 isolates possessed H7, shigatoxins 1-2, or enterohemolysin genes, whereas all the broiler isolates and one of the human isolates were positive for intimin gene. In the PFGE analysis, a total of eight different profiles (four from broiler and four from human isolates) were observed. However, there were no genetic relationships between broiler and human E. coli O157 isolates. It can be concluded that more detailed studies are needed in poultry to better understand the role of these species in the epidemiology of E. coli 0157 infections in humans.
Keywords: Field Gel-Electrophoresis; Multiplex Pcr Assays; Turkish Children; Virulence Genes; Poultry; Prevalence; Gastroenteritis; Identification; Salmonella; Slaughter